When serial letter processing implies a facilitative length effect. - Whitney, Carol (Language, Cognition & Neuroscience, 2018)
Most researchers who study visual word recognition assume that an inhibitory length effect (slower Reaction Times for longer words) indicates serial letter processing, while absence of a length effect indicates parallel letter processing. This article discusses why the latter assumption is incorrect. In particular, the SERIOL and SERIOL2 models of orthographic processing imply that, for a specific stimulus configuration, the proposed serial letter processing should yield faster Reaction Times for longer words in the lexical-decision task. Published experimental data confirm this surprising implication, providing strong support for the serialisation mechanism of the SERIOL models.